Determination of organophosphorus residue in three different types of vegetable crops by gas chromatography mass spectrometry / Norhamsharina Hamdan - Hamdan, Norhamsharina (Faculty of Applied Sciences, 2009)
The purpose of this study is to determine the organophosphate residue in three different types of crops of vegetables by gas chromatography mass spectrometer. The three types of crops are representing their group of crops. Potatoes are in-soil product, cabbages are crops on- soil and tomatoes are aerial product. From the analysis, di-n-othyl phatalate were detected in these three types of crops. The highest residual concentration was detected in-soil vegetation represented by potato, followed by cabbage and tomato. Cabbage showed the moderate number of peak and then tomato showed the lower number of peak. The confident level of potato is 59%, cabbage is 72% and tomato is 72%.